Identification of Mangrove Ecosystem Damage in the PLTD Poka Area, Ambon City - Sairmorsa, Wanti; Tetelepta, Edward Gland (GEOFORUM, 2024)
Indonesia, home to the largest mangrove ecosystem in the world, plays a vital ecological, socio-economic, and socio-cultural role. Mangrove forests, as tropical coastal vegetation communities, grow in tidal areas, providing coastal protection, fish resources, and various ecological benefits. However, mangrove forests are vulnerable to damage from human activities, such as overexploitation and waste disposal. Development demands, particularly the conversion of mangrove forests, lead to ecosystem degradation. Physical, chemical, biological, and socio-economic factors contribute to this damage, with oil pollution and waste disposal posing severe threats. The importance of conservation and sustainable management is emphasized to maintain the sustainability of mangrove ecosystems. This research employs qualitative methods with descriptive and experimental approaches. The descriptive approach is used to understand the research object in its natural conditions, while the experiment is conducted systematically and planned to prove theories. The research approach involves a combination of quantitative methods and qualitative interviews to understand the interaction of research variables deeply. Based on the research findings, factors that need to be considered in mangrove areas include physical, chemical, biological, and social aspects. Physical and chemical parameters, such as temperature, salinity, and water quality, meet the maximum allowable standards. However, there is an increase in heavy metals, mainly dissolved oil, which could threaten the health of the mangrove ecosystem. Changes in mangrove species were also detected, indicating a threat to the sustainability of mangrove plants. Social issues, such as indiscriminate disposal of plastic waste, wood, and glass shards, cause blockages and hinder mangrove growth. Therefore, efforts for protection and sustainable management are necessary to ensure the sustainability of the mangrove ecosystem in the area.